Kritik Sosial terhadap Budaya Patriarki dalam Novel The Mango Season Karya Amulya Malladi - Haidar Dhiya Ulhaq; Erik Candra Pertala (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
Patriarchal culture remains a significant social issue that influnces women’s lives, particurarly in relation to marriage, family authority, and gender expectations literary works often reflect these social realities and serve as a mendium for criticizing social inequality. This study aims to analyze the representation of patriarchal culture and the social criticism of patriarchy portrayed in Amulya Malladi’s novel The Mango Season. This research employed a qualitative descriptive method using the sociology of literature approach and Marxist feminist perspective. The data were collected through intensive reading and note-taking techniques, focusing on narrative descriptions and dialogues related to patriarchal practices. The findings reveal that patriarchal culture is represented through family control over women’s marital decisions, the expectation that women must marry to achieve happiness, the persistence of dowry practices, and social standards that evaluate women based on age, appearance, and marital status. Furthermore, the novel presents social criticism by exposing the limitations imposed on women’s autonomy and highlighting their resistance to patriarchal norms. The study implies that literary works can function as a critical medium for raising awareness of gender inequality and encouraging more equitable social relations in contemporary society.